eHealth Tools to Provide Structured Assistance for Atrial Fibrillation Screening, Management, and Guideline‐Recommended Therapy in Metropolitan General Practice: The AF‐SMART Study - Orchard, Jessica; Neubeck, Lis; Freedman, Ben; Li, Jialin; Webster, Ruth; Zwar, Nicholas; Gallagher, Robyn; Ferguson, Caleb; Lowres, Nicole (Journal of the American Heart Association, 2019)
Background This eH ealth implementation study aimed to evaluate strategies to promote opportunistic atrial fibrillation ( AF ) screening using electronic screening prompts and improve treatment using electronic decision support ( EDS ) software. Methods and Results An electronic screening prompt appeared whenever an eligible patient's (aged ≥65 years, no AF diagnosis) medical record was opened in participating general practices. General practitioners and practice nurses offered screening using a smartphone ECG, with validated AF algorithm. Guideline-based EDS was provided to assist treatment decisions. Deidentified data were collected from practices using a data extraction tool. General practices (n=8) across Sydney, Australia, screened for a median of 6 months. A total of 1805 of 11 476 (16%) eligible patients who attended were screened (44% men, mean age 75.7 years). Screening identified 19 (1.1%) new cases of AF (mean age, 79 years; mean CHA DS - VAS c, 3.7; 53% men). General practitioners (n=30) performed 70% of all screenings (range 1-448 patients per general practitioner). The proportion of patients with AF who had CHA DS - VAS c ≥2 for men or ≥3 for women prescribed oral anticoagulants was higher for those diagnosed during the study: 15 of 18 (83%) for screen-detected and 39 of 46 (85%) for clinically detected, compared with 933 of 1306 (71%) patients diagnosed before the study ( P<0.001). The EDS was accessed 111 times for patients with AF and for 4 of 19 screen-detected patients. Conclusions The eH ealth tools showed promise. Adherence to guideline-based oral anticoagulant prescription was significantly higher in patients diagnosed during the study period, although the EDS was only used in a minority. While the proportion of eligible patients screened and EDS use was relatively low, further refinements may improve uptake in clinical practice. Clinical Trial Registration URL : www.anzctr.org.au . Unique identifier: ACTRN 12616000850471.